Study of Potential Development of Goat and Sheep in North Labuhanbatu Regency - Syahrul Anwar; E Mirwhandono; T H Wahyuni; S Sepriadi (Talenta Publisher, 2020)
North Labuhanbatu regency is one of the districts in North Sumatra Province that has the potential in the development of livestock and agriculture sectors. This research aims to find out the potential of agriculture and plantation waste as well as areas that can be used as a development area for goat and sheep livestock in North Labuhanbatu regency. The type of research used is descriptive research to describe the potential of agriculture and plantation waste in determining the development area of goat and sheep livestock using LQ methods combined with livestock density, waste support index, and capacity to increase ruminants livestock population. This reserach was conducted in North Labuhanbatu regency in February – April 2020. The results showed that North Labuhanbatu regency has development potential in supporting North Sumatra Province a producer of goat and sheep livestock. Regional strategy I (distribution area) namely Aek Natas Sub-District, Kualuh Hilir, Kualuh Leidong. Regional strategy group II (strengthening region) namely Na IX-X, Aek Kuo, Kualuh Selatan and Kualuh Hulu sub-districts. Group III strategy (supporting region) namely Marbau subdistrict. Alternative strategies for utilizing agriculture and plantation waste in the development of goat and sheep livestock one of them is the integration system in order to use crop waste as a source of animal feed in North Labuhanbatu regency.